Inovasi Pembelajaran Al-Qur’an Pada Masa Pandemi Covid-19 diSMP Techno Insan Kamil Tuban - Hibrul Umam (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
Abstraks : This study aims to describe the implementation of the application of the Qur'anic learning method before and during the Covid-19 pandemic. The use of offline or online learning methods is adjusted to the conditions of the spread of Covid-19. The online methods include video calls, voice calls and voice notes. (3) Supporting factors in learning the Qur'an during the Covid-19 pandemic at SMP Techno Insan Kamil Tuban are qualified educators or clerics, motivation of students to learn the Qur'an, parental support to encourage their children to take part in the study hours and internet data package assistance from the foundation. The obstacle to the implementation of Al-Qur'an learning during the Covid-19 pandemic for class VIII students at SMP Techno Insan Kamil Tuban is when online it is difficult to condition students who are at home to recite the Koran due to lack of parental control in paying attention to children to recite the Koran, lack of discipline. students in taking online Koran lessons, lack of student motivation for Koran lessons because they are more concerned with general subjects so that they recite only modestly, Students do not pay attention to corrections from asatidz. And the obstacle when offline learning is the lack of time in recitation activities because offline the teacher teaches students with different Koran achievements, students sometimes talk alone because they have been at home for long and have never met their friends and the lack of student motivation in the Koran so that they sometimes do not bring students' sense of connection books or students' memorization books. (4) (a) Solutions to overcome obstacles during online learning are: Establishing good communication with all guardians to support learning activities at home by controlling their children to always follow learning regularly offline, always registers students who participate or do not participate in online learning so that teachers can take action for students who have never participated in online learning, provide motivation to parents and guardians about the importance of the Koran so that parents pay special attention to learning the Koran, motivate students to be important The importance of being able to recite the Koran so that students are diligent in participating in Koran learning, always changing the online learning method if there is one method that is not appropriate, the ustadz always records student achievements every day and students are given achievement cards written by students themselves. (b) Solutions to overcome obstacles during offline learning are: Time management in reciting activities by adjusting the number of students and the level of difficulty of students in reading the Koran. provide classroom rules to students so that learning becomes conducive. always remind students not to bring a sense of connection book when reading the Koran.